Cost-effectiveness analysis of forest ecosystem services in mountain areas in Afghanistan. (September 2021) - Gouhari, Saeeda; Forrest, Alan; Roberts, Michaela
Abstract: Mountain areas provide essential ecosystem services for communities living nearby. However, increasing demands for resources have led to the gradual clearing of biodiverse mountain areas worldwide. Providing an alternative and sustainable livelihood source, such as forestry, could support natural regeneration and counter this process. In order to better understand future land-use, an assessment of forestry's impact on available ecosystem services functioning needs to be conducted. This paper analyzes the cost-effectiveness of forest plantation on marginal lands to promote ecosystem services restoration in Shah Foladi Protected Area, Afghanistan, using a methodology combining ecosystem services mapping, and analysis of crucial ecosystem services. We account for timber production, fuelwood provision and carbon sequestration as important benefits of forestry in mountain areas. To our knowledge this represents the first account of ecosystem services in Afghanistan, providing an important first step in accounting for natural capital in the country, with transferable lessons to other countries in post-conflict recovery and peacebuilding setting, as well as other mountain areas worldwide. The result of the study forms a basis for economic valuation of these ecosystems services and inform land-use management decision making. Our findings show that planting trees and establishing forests would increase timber and fuelwood production and support alternative livelihood sources for communities, alleviating land degradation, which ultimately would support the conservation of the natural landscapes. The analysis reveals that planting trees on marginal land is economically justifiable at over ten years in the majority of the Shah Foladi valleys, and the result is positive even where the very conservative 9.5% discount rate is applied. Highlights: Marginal lands support ecosystem restoration and sustainable community livelihoods. Ecosystem services' economic valuation improves sustainable environment management. Forest ecosystem services allows natural regeneration of rangelands and wilderness. Ecosystem services' valuation supports better decision-making in investment. Plantation is economically justifiable at a discount rate of 3.5% over 10 years.